Role of Diabetes in the Development of Acute Respiratory Distress Syndrome - Yu, Shun (2013)
OBJECTIVES: Diabetes has been associated with decreased development of acute respiratory distress syndrome in some, but not all, previous studies. Therefore, we examined the relationship between diabetes and development of acute respiratory distress syndrome and whether this association was modified by type of diabetes, etiology of acute respiratory distress syndrome, diabetes medications, or other potential confounders. DESIGN: Observational prospective multicenter study. SETTING: Four adult ICUs at two tertiary academic medical centers. PATIENTS: Three thousand eight hundred sixty critically ill patients at risk for acute respiratory distress syndrome from sepsis, pneumonia, trauma, aspiration, or massive transfusion. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Diabetes history was present in 25.8% of patients. Diabetes was associated with lower rates of developing acute respiratory distress syndrome on univariate (odds ratio, 0.79; 95% CI, 0.66–0.94) and multivariate analysis (adjusted odds ratio, 0.76; 95% CI, 0.61–0.95). After including diabetes medications into the model, diabetes remained protective (adjusted odds ratio, 0.75; 95% CI, 0.59–0.94). Diabetes was associated with decreased development of acute respiratory distress syndrome both in the subgroup of patients with sepsis (adjusted odds ratio, 0.77; 95% CI, 0.61–0.97) and patients with noninfectious etiologies (adjusted odds ratio, 0.30; 95% CI, 0.10–0.90). The protective effect of diabetes on acute respiratory distress syndrome development is not clearly restricted to either type 1 (adjusted odds ratio, 0.50; 95% CI, 0.26–0.99; p = 0.046) or type 2 (adjusted odds ratio, 0.77; 95% CI, 0.60–1.00; p = 0.050) diabetes. Among patients in whom acute respiratory distress syndrome developed, diabetes was not associated with 60-day mortality on univariate (odds ratio, 1.11; 95% CI, 0.80–1.52) or multivariate analysis (adjusted odds ratio, 0.81; 95% CI, 0.56–1.18). CONCLUSIONS: Diabetes is associated with a lower rate of acute respiratory distress syndrome development, and this relationship remained after adjusting for clinical differences between diabetics and nondiabetics, such as obesity, acute hyperglycemia, and diabetes-associated medications. In addition, this association was present for type 1 and 2 diabetics and in all subgroups of at-risk patients.